2012
DOI: 10.1177/0255761411431391
|View full text |Cite
|
Sign up to set email alerts
|

Fostering musical creativity in pre-service teacher education: Challenges and possibilities

Abstract: Research regarding music teaching in primary school reveals generalist teachers' and student teachers' low musical abilities and low confidence in teaching Music, and even more, in including creative activities in music teaching. This article reports on a study which sought to create a fruitful and supportive environment that would allow 64 primary school student teachers participating in a sound stories' project, to unearth their creative skills and abilities, through active participation and direct experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Emotions may intensify the resistance to change, but at the same time constitute potential levers to modify or replace beliefs. Working with student teachers for primary school, Stavrou ( 2012 ), for example, reports on a collaborative creative music training project that was designed to understand and change student teachers' beliefs in relation to musical creativity. More in particular the project was motivated by the well-documented fi nding that generalist teachers tend to have little confi dence in their own musical capabilities as well as in their ability to teach music to children (Stavrou, 2012 , p. 48).…”
Section: Emotions and Beliefsmentioning
confidence: 99%
“…Emotions may intensify the resistance to change, but at the same time constitute potential levers to modify or replace beliefs. Working with student teachers for primary school, Stavrou ( 2012 ), for example, reports on a collaborative creative music training project that was designed to understand and change student teachers' beliefs in relation to musical creativity. More in particular the project was motivated by the well-documented fi nding that generalist teachers tend to have little confi dence in their own musical capabilities as well as in their ability to teach music to children (Stavrou, 2012 , p. 48).…”
Section: Emotions and Beliefsmentioning
confidence: 99%
“…Specifically, current studies have shown that Greek early childhood educators seem to have limited knowledge on the use of music as a teaching tool in their classrooms and they may end up feeling unprepared or insecure when implementing music in the school's daily routines (Chrysostomou et al, 2007;Koutsoupidou, 2010). Similarly, studies that investigated Greek and Cypriot pre-service teachers' academic music training in relation to their levels of confidence for teaching music in their classrooms, reported that pre-service teachers lack practical experience and adequate preparation in teaching music, which may affect their levels of selfefficacy, enthusiasm, and creativity for implementing music activities in their classrooms (Economidou-Stavrou, 2013;Koutsoupidou, 2010).…”
Section: Aim Of the Studymentioning
confidence: 99%
“…The aforementioned disconnection between beliefs and practices may be a reflection of the need for more training and support on how to use music in a variety of situations for young children with autism. Literature on teacher preparation highlights the needs for experiential learning and well-structured practicum to assist teachers in implementing music in their classrooms (Economidou, 2013). Early childhood educators typically attend courses and training about specific music approaches (such as Suzuki, Orff, and Dalcroze) but they do not feel confident about their training and practicum experience when implementing music activities in the classroom (Economidou & Telemachou, 2006;Telemachou, 2007).…”
Section: Use Of Music Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of previous research with primary and secondary school students in Cyprus suggest that there was no alignment between student preferences and what was taught in the music classroom (Economidou Stavrou, 2004, 2006; Teklos, 2011), revealing a negative attitude toward music as a school subject (Economidou Stavrou, 2004, 2006; Forari, 2005; Teklos, 2011). Following the publication of this research, Cyprus undertook a wide educational reform, including the design and development of a new national curriculum for all school subjects (MOEC, 2010, 2016).…”
mentioning
confidence: 95%